Environment and properties of obscured and unobscured active galactic nuclei - Taormina, Mónica (2013)
Abstract: We analyze the properties of obscured and unobscured active galactic nuclei selected using mid-infrared colors in the redshift range 1 < z < 3. We find that obscured objects are located in a denser local galaxy environment compared to the unobscured sample.